2014
DOI: 10.3747/pdi.2012.00328
|View full text |Cite
|
Sign up to set email alerts
|

Can Dialysis Patients be Accurately Identified using Healthcare Claims Data?

Abstract: ♦ Background: While health insurance claims data are often used to estimate the costs of renal replacement therapy in patients with end-stage renal disease (ESRD), the accuracy of methods used to identify patients receiving dialysis -especially peritoneal dialysis (PD) and hemodialysis (HD) -in these data is unknown. ♦ Methods: The study population consisted of all persons aged 18 -63 years in a large US integrated health plan with ESRD and dialysis-related billing codes (i.e., diagnosis, procedures) on health… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 7 publications
0
7
0
Order By: Relevance
“…A recent meta-analysis of the validity of heart failure diagnoses in administrative data sets suggests that the specificity and positive predictive value of these codes are high but with low sensitivity. 7 Other studies have shown that the positive predictive value of ICD codes is highly variable [8][9][10][11] but also that the performance of these codes may be improved by the application of algorithms or the addition of multiple associated billing codes or further clinical information, such as we have tried to include. 8,12 Notably, the current investigation examined the specificity of ACHD codes but not the sensitivity, given the lack of ability to identify the total number of ACHD patients across the hospital system.…”
Section: Discussionmentioning
confidence: 99%
“…A recent meta-analysis of the validity of heart failure diagnoses in administrative data sets suggests that the specificity and positive predictive value of these codes are high but with low sensitivity. 7 Other studies have shown that the positive predictive value of ICD codes is highly variable [8][9][10][11] but also that the performance of these codes may be improved by the application of algorithms or the addition of multiple associated billing codes or further clinical information, such as we have tried to include. 8,12 Notably, the current investigation examined the specificity of ACHD codes but not the sensitivity, given the lack of ability to identify the total number of ACHD patients across the hospital system.…”
Section: Discussionmentioning
confidence: 99%
“…The meaning of this study is to identify the actual burden on ESRD because the cost studies in the past have been based on insurance claims data [17,[29][30][31][32][33][34]. The detailed meaning is as follows.…”
Section: Discussionmentioning
confidence: 99%
“…The meaning of this study is to identify the actual burden on ESRD because the cost studies in the previous have been based on insurance claims data [17,[29][30][31][32][33][34]. The detailed meaning is as follows.…”
Section: Discussionmentioning
confidence: 99%